1989
DOI: 10.1002/cyto.990100312
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral variations in dna distribution patterns in mammary adenocarcinomas

Abstract: Correlated flow-cytometric (FCM) and microspectrophotometric (MSP) techniques were applied to investigating whether intratumoral variations in the DNA distribution patterns of 21 primary mammary adenocarcinomas can occur. Although neoplastic cell populations with both diploid and tetraploid (i.e., euploid) distribution patterns could be found in varying proportions in some of the tumors, there was no evidence in any tumor nodule for the presence of euploid populations in one part and aneuploid populations in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…Some studies have demonstrated that intratumor heterogeneity may exist in some types of tumors, particularly in breast cancers (16)(17)(18)(19). DNA content heterogeneity within individual tumors has also been reported in colonic adenocarcinoma (201, lung cancers (21), transitional cell cancers of the bladder (23, and prostatic adenocarcinomas (23).…”
Section: Samplingmentioning
confidence: 99%
“…Some studies have demonstrated that intratumor heterogeneity may exist in some types of tumors, particularly in breast cancers (16)(17)(18)(19). DNA content heterogeneity within individual tumors has also been reported in colonic adenocarcinoma (201, lung cancers (21), transitional cell cancers of the bladder (23, and prostatic adenocarcinomas (23).…”
Section: Samplingmentioning
confidence: 99%
“…In the following, the tubular and tubuloductal carcinomas are abbreviated TD, followed by + sign(s) or 0, whereas ductal carcinomas of comedo type are abbreviated comedo. In parallel with the morphological assessment, the amount of non-cancerous cells (mesenchymal tissue), as a proportion of the total cell content, was recorded, the results being divided into four groups (1)(2)(3)(4): group 1, 0-25%; group 2, 26-50%; group 3,51-75%; and group 4, 76-100%.…”
Section: Histopathology (4-biopsy Series Only)mentioning
confidence: 99%
“…However, in other studies where the DNA ploidy of specimens from different areas of resected tumours were compared, only small differences between the samples were seen. It was concluded that different results are not likely to be attributed to intratumoral DNA heterogeneity but to differences in the methods used [37,38]. In the present study, a flow cytometric method for routine determination of the DNA ploidy of cells obtained by forceps biopsies from patients with oesophageal cancer was developed.…”
Section: Representativeness Of Forceps Biopsiesmentioning
confidence: 99%